Sejarah peradaban Islam di Indonesia - Yusuf, Mundzirin (Yogyakarta : Penerbit Pustaka, 2006)
History of Islamic civilization in Indonesia, ca. 13th century to ca. 2002; collection of articles
Daftar pustaka : p. 303
Keywords: Islam -- Indonesia -- Civilization; Civilization, Islamic